Depression and sleep quality among nurses in a tertiary hospital in Bangkok - Junsatitanon, Pariyanuch; Pongpirul, Krit (Chulalongkorn Medical Journal, 2021)
Background: Currently, depression is a mental health problem that tends to increase. Nurses are one of the healthcare workers that are at risk of depression. The cause of which is due to their heavy workload. In addition, shift work results in decreased sleeps quality. Moreover, research studies on the relationship between sleep quality and depression including other factors are few. Objectives: To investigate the relationship between sleep quality and depression including the prevalence of depression and its associated factors. The recruited subjects of the study were nurses who worked at Nopparat Rajathanee Hospital in 2019. Methods: A cross-sectional survey of 638 nurses was conducted in this study. Depression was assessed by a Patient Health Questionnaire-9 (PHQ-9) Thai version and sleep quality was assessed by self-administered questionnaire adapted from the Pittsburgh sleep quality index (PSQI). Prevalence of depression and the sleep quality assessment results are presented in percentage while the associated factors are presented by crude and adjusted odds ratios (ORs). Results: The study has found a significant association between sleep quality and depression. Most subjects (61.0%) had poor sleep quality and the poor quality of sleep was depressed 3.38 times. The prevalence of depression in subjects was 17.3%. The factors associated with depression included: exercise, body mass index, job satisfaction, receiving welfare and support from the leader and sleep quality. Conclusion: Sleep quality affects the occurrence of depression including associated factors that may aggravate more depressive symptoms. This study provides information leading to planning and guidelines for solving psychological problems.